Dearomatizing Conjugate Addition to Quinolinyl Amidines for the Synthesis of Dehaloperophoramidine through Tandem Arylation and Allylation1. Issue 39 (9th August 2013) - Ishida, Takayuki; Ikota, Hideo; Kurahashi, Kei; Tsukano, Chihiro; Takemoto, Yoshiji
<x xml:space="preserve">Abstract</x> Dehaloperophoramidine, the dehalogenated analogue of the marine hexacyclic alkaloid perophoramidine was synthesized. The intramolecular nucleophilic dearomatizing arylation of aminoquinoline initiated by a lithium–iodine exchange and the subsequent direct allylation of the resultant azaenolate afforded a pentacyclic bisamidine compound bearing two contiguous all‐carbon quaternary centers in good yield with excellent diastereoselectivity.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>